Clinical application of gancyclovir in the complex treatment of the different forms of true acantholytic pemphigus - M. K. Baltabaev; A. M. Baltabaev (Vestnik Dermatologii i Venerologii, 2017)
Short summary and results of the own clinical observations on efficacy of developed complex method on the treatment of true acantholytic pemphigus composed of traditional immunosuppressive therapy and antiviral remedy - gancyclovir are presented. The etiology of herpesvirus infection had been discussed in the pathogenesis of the disease.